Fecal Coliform Bacteria Distribution in the Coastal Waters of Port Dickson - Law , A.T; Othman, Azhar (1985)
The distribution of fecal coliform bacteria in the coastal waters of Port Dickson was studied between March and August, 1984. Seventeen sampling stations were selected between Port Dickson town and Blue Lagoon, which covered a distance of 17 km. Very high counts of the bacteria were detected closer to the town area and high counts were found up to 5 - 6 km along the coast from the town. The rest of the stations had counts below 1000 MPN11 00 ml during high tide. Some of the ares contained very low counts and can be considered safe for recreational purposes.